Analysis of factors that influence the level of customer satisfaction at PT. Trakindo Utama Palembang - Desfitrina, Desfitrina; Bassi, Aliming; Zulfadhli, Zulfadhli; Rusdianto, Rusdianto; Nugraha, Petera (BIMA Journal (Business, Management, & Accounting Journal), 2023)
The purpose of this research was to determine the analysis of factors that influence the level of customer satisfaction at PT. Trakindo Utama Palembang. The analysis technique used in this research is a multiple linear analysis method with a qualitative descriptive approach which is quantitatively assisted with the SPSS tool. Quantitative qualitative data is included in inferential statistics, this statistics is generally used to analyze quantitative data (interval data or ratio data) but often qualitative data is also analyzed through inferential statistics, but qualitative data is first quantified by providing score or weight on the qualitative data. The product (X1) obtained a t count of 1.092 with a significance level of 0.283 which is greater than 0.05. This means that Product (X1) does not have a significant effect. The price (X2) can be calculated at 2.166 with a significance level of 0.038 which is smaller than 0.05. This means that price (X2) has a significant effect. Place (X3) can be calculated as 1.366 with a significance level of 0.181 which is greater than 0.05. Means Place (X3) has no effect. Promotion (X4) can be calculated at 2.654 with a significance level of 0.012 from 0.05. This means that Promotion (X4) has a significant effect.